Supply chain integration and halal frozen meat product returns - Fernando, Yudi; Jasmi, Muhamad Fairuz Ahmad; Wahyuni-TD, Ika Sari; Mergeresa, Fineke; Khamis, Kamarul Azman; Fakhrorazi, A; Omar, Rusdi (Emerald Publisher, 2022)
Purpose: Halal frozen meat product returns are major challenges in the halal frozen meat supply chain because of the sheer volume and processing costs of returns. The purpose of this paper is to investigate the effect of integrated halal supply chain (IHSC) strategies on effective product returns with halal logistics (HL) as an interceding variable. Design/methodology/approach: This paper used the cross-sectional technique to select samples from a population that revolved around the halal food industry in Malaysia. Data collected from halal service providers who handle halal frozen meat product returns provided insightful findings. Findings: The findings of this paper indicate that the IHSC dimensions, such as interactive fairness, procedural fairness and service coverage, are positively associated with effective product returns. It also shows that HL plays a mediating role between the IHSC and effective product returns. Practical implications: From a practical viewpoint, this paper suggests that an effective return service system can be designed to emphasise the category of interactive and flexible justice services through refunds or product replacement, depending on customer's demand. Originality/value: The result of this paper provides insights into how logistics service provider managers effectively and efficiently handle the halal supply chain network when involving product returns.